2021
DOI: 10.1021/acsbiomaterials.0c01392
|View full text |Cite
|
Sign up to set email alerts
|

Design and Compressive Fatigue Properties of Irregular Porous Scaffolds for Orthopedics Fabricated Using Selective Laser Melting

Abstract: An irregular porous structure plays a major role in bone tissue engineering, and it is more suitable for bone tissue growth than a regular porous structure. The response surface method was used to establish a relationship between the average pore size and the design parameters. The technology of selective laser melting was utilized to fabricate the porous Ti-6Al-4V scaffolds with an irregularity of (0.4) and porosities of (70, 80, and 90%) designed using the Voronoi-tessellation method. Compression tests of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Structural characteristics and mechanical parameters of the two scaffolds obtained from the compressive test and response surface prediction are listed in Table . The results showed that positive and negative deviations between predicted and test values are both less than 10%. , As a result, model regression equations can accurately predict structural characteristics and mechanical parameters of scaffolds when unit cell design factors are V ϵ [3, 9], F 1 ϵ [0.2, 0.6], and F 2 ϵ [0.2, 0.6].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Structural characteristics and mechanical parameters of the two scaffolds obtained from the compressive test and response surface prediction are listed in Table . The results showed that positive and negative deviations between predicted and test values are both less than 10%. , As a result, model regression equations can accurately predict structural characteristics and mechanical parameters of scaffolds when unit cell design factors are V ϵ [3, 9], F 1 ϵ [0.2, 0.6], and F 2 ϵ [0.2, 0.6].…”
Section: Resultsmentioning
confidence: 95%
“…Irregular porous scaffolds designed using Voronoi tessellation exhibited a certain degree of randomness that resulted in large processing deviations according to distributions of random points because local pore and strut diameters failed to meet manufacturing requirements from the perspective of design. , Local modeling was used as the main method, and the Voronoi unit cell was established using three independent design factors in this study. The unit cell structure divided by the equal volume of Voronoi was anisotropic, that is, the unit cell structure had different structural properties in planes XOY, YOZ, and XOZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It requires CT scanning of bone tissue to obtain the 3D structure of bone trabeculae, which are then rotated, stitched, and superimposed to achieve the overall design of the pore structure ( Cheng et al, 2014 ). Alternatively, by employing Voronoi structures, it generates randomly distributed points within the spatial structure under certain conditions in a functional manner, subsequently forming pore structures with unspecified arrangements by connecting points to points ( Deering et al, 2021 ; Zhao et al, 2021 ; Zhu et al, 2021 ). In addition to the above structures, the gradient pore structure has gradually become a research hotspot in recent years as the knowledge of the pore structure of bioengineered porous bone tissue materials has gradually deepened.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the built struts were larger than the designed thickness, and the struts of 0q were thicker than the struts of 90q. Zhu et al conducted a fatigue test on porous scaffolds and found that the fatigue property was greatly affected by the porosity and heat treatment process [7]. However, there is a lack of research work on the stress concentration in the porous structures from additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%